THE INTERNAL FAKTORS EFFECT ON QUALITY OF HOUSEHOLD INVESTORS' FINANCIAL DECISIONS - Alistraja Dison Silalahi; Cita Ayni Putri Silalahi; Rukmini; Mohd. Idris Dalimunthe (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The study targets to research the effect of tension, autonomy, impulsivity, financial attitudes on monetary choice making with monetary capability as mediation and virtual financial literacy as moderation, an analysis study of family traders in North Sumatra. This research is quantitative studies, causality. The records analysis method uses partial least rectangular statistical analysis. The consequences found that monetary tension and attitudes have a high-quality impact on economic functionality and financial decision making. economic autonomy and impulsivity have no effect on monetary functionality and monetary choice making. financial functionality has a superb impact on monetary choice making. virtual economic literacy has a nice impact on economic capability. financial functionality mediates the influence ofmonetary anxiety and attitude on financial decision making. monetary functionality does now not mediate the impact of financial independence and spontaneity on economic planning. virtual financial literacy moderates the influence of monetary anxiety, monetary autonomy, impulsivity, economic attitudes on monetary capability. The implication of the research consequences is a advice to the Indonesia stock exchange North Sumatra location to be a solution to literate the public regarding digital finance, especially housewives who are busy taking care of the family.